Impact Of Information Technology (It) Tools, Partner Relationship And Supply Chain Performance - Ramayah T, Ramayah T; Tan , Yen Sang; Omar, Roaimah; Md. Dahlan, Noornina (Asian Academy of Management (AAM), 2008)
This paper proposes a model that assesses the usage of information technology (IT) tools, commitment of partner relationships, and supply chain performance in the Malaysian manufacturing industry. A total of 250 questionnaires were distributed to manufacturing companies located in Penang, which is in the northern region of Malaysia. Applying multiple regression analysis, the study indicated that a higher level of supply chain partner commitment leads to a higher level of supply chain reliability and flexibility. Trust among supply chain partners also contributes to improving supply chain flexibility. The study focused only on inter-organisational relationships. Future research should examine how both inter- and intra-organisational collaboration impact supply chain performance. Although researchers have recognised that IT is an enabler of supply chain management (SCM) activities, there has been limited research that has directly associated the usage of IT and partner relationships to supply chain performance. This research is essential in order to ascertain the impact of IT usage and partner relationships on improving supply chain performance, particularly in the Malaysian manufacturing environment.